Balloon catheter ablation to treat paroxysmal atrial fibrillation: what is the level of pulmonary venous isolation? - Reddy, Vivek Y; Neuzil, Petr; d'Avila, Andre; Laragy, Margaret; Malchano, Zachary J; Kralovec, Stepan; Kim, Steven J; Ruskin, Jeremy N (Heart rhythm, 2008)
BACKGROUND: Unlike the initial balloon ablation catheters that were designed to deliver ablation lesions within the pulmonary veins (PVs), the current balloon prototypes are fashioned to deliver lesions at the PV ostia. OBJECTIVE: Using electroanatomical mapping, this study evaluates the actual location of ablation lesions generated by cryo-based, laser-based, or ultrasound-based balloon catheters. METHODS: In a total of 14 patients with paroxysmal atrial fibrillation, PV isolation was performed using either a cryoballoon catheter (8 patients), laser catheter (4 patients) or ultrasound balloon catheter (2 patients). Patients underwent preprocedural computed tomographic/magnetic resonance imaging. An intracardiac ultrasound catheter was used to aid in positioning the balloon catheter at the PV ostium/antrum. In all patients, sinus rhythm bipolar voltage amplitude maps (using either CARTO with computed tomographic/magnetic resonance image integration or NavX mapping) were generated at baseline and after electrical PV isolation as confirmed by use of a circular mapping catheter. RESULTS: Electrical isolation was achieved in 100% of the PVs. Electroanatomical mapping revealed that after ablation with any of the 3 balloon catheters, the extent of isolation included the tubular portions of each PV to the level of the PV ostia. However, the PV antral portions were left largely unablated with all 3 balloon technologies. CONCLUSION: Using the current generation of balloon ablation catheters, electrical isolation occurs at the level of the PV ostia, but the antral regions are largely unablated.
Keywords: Electrophysiologic Techniques, Cardiac; katetrizace; počítačová rentgenová tomografie; Magnetic Resonance Imaging; Catheterization; magnetická rezonanční tomografie; endoskopie; Humans; laserová terapie; echokardiografie; venae pulmonales; Echocardiography; výsledek terapie; lidé; Atrial Fibrillation; Endoscopy; katetrizační ablace; Laser Therapy; elektrofyziologické techniky kardiologické; Cryotherapy; Tomography, X-Ray Computed; Pulmonary Veins; Treatment Outcome; Catheter Ablation; fibrilace síní; kryoterapie